Pendampingan Pendidikan Karakter Disiplin Melalui Pembiasaan Salat Dhuha di SMP IT Kreatif Rejang Lebong - Mirzon Daheri; Fitria (Yayasan Darusssalam Bengkulu, 2025)
Worship is a form of self-sacrifice to Allah SWT which serves to get closer to Him. In general, worship is divided into two types, namely mahdhah worship (pure ritual) and ghairu mahdhah worship (social ritual). One form of mahdhah worship that has high spiritual value is prayer, which in Arabic is called asshalatu, meaning prayer. Prayer is divided into two categories, namely obligatory prayers and sunnah prayers. Among the various forms of sunnah prayers, the dhuha prayer is one of the prayers commonly performed by Muslims. The dhuha prayer has various virtues, including fulfilling spiritual needs, strengthening beliefs, building norms and morals, and instilling disciplinary values in students' lives. Consistent implementation of dhuha prayer can help shape an attitude of order, responsibility, and regularity, both in the context of worship and in students' social lives. This study used a descriptive qualitative approach, with data collection methods through interviews, observation, and documentation. The research subjects included principals, teachers, and students at Rejang Lebong Creative IT Junior High School, using source triangulation techniques to ensure data validity. The results showed that the implementation of dhuha prayer in congregation at school is able to instill positive habits in students, especially in terms of discipline and responsibility. The dhuha prayer schedule set by the school is one of the strategic steps in building the character of students who are religious, disciplined, and have responsibility for themselves and their environment. This finding is expected to contribute to the development of an integrated worship habituation model in the formal education system, especially in the context of student character building in accordance with Islamic values.